Generation and Validation of Crack Growth Resistance Curve from DCB Specimens: An Experimental Study - Alfred Franklin, V.; Christopher, T. (Проблемы прочности, 2013)
This article examines fracture toughness and interlaminar failure load of double cantilever beam (DCB) specimens made of glass/epoxy of three different lay-ups. The present model requires the applied load–displacement history and crack extension to generate the crack growth resistance curve (R-curve). From the generated R-curve, the interface failure load was estimated for the specimens and good agreement with the experimentally recorded value was found.